12. ANALISIS RESPON INDONESIA TERHADAP AUSTRALIA DALAM PERISTIWA PENCEMARAN LAUT KILANG MINYAK MONTARA TAHUN 2009 - Caliptra, Ghiebiel Fido; Susiatiningsih, Hermini; Basith Dir, Andi Akhmad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
Montara oil refinery marine pollution which comes from Australia enter Indonesia’s seaand inflict disadvantage, that make Indonesia to seek compensation on Australia but notsucceeded. Indonesia and Australia ratified Memorendum of Understanding 1996 onrespond and preparedness marine pollution, but Australia did not use three paragraphs inMoU 1996 when Montara marine pollution happened. Indonesia should seek compensationbe based on three paragraphs in MoU 1996 which did not use by Australia but Indonesianot did it. This study tries to analize Indonesia respond’s which did not use MoU 1996 toseek compensation on Australia. The research method which used to explain of Indonesiarespond’s is explanative analytical research and found the Indonesia repond’s which didnot use MoU 1996 to seek compensation on Australia is a form of compromise. Thecompromise used by Indonesia to keep stability relations with Australia because bothcountry had a mutual relations.